Betulin-3,28-diphosphate as a Component of Combination Cytostatic Drugs for the Treatment of Ehrlich Ascites Carcinoma In Vitro and In Vivo Experiments - Olga Vorobyova; Olga Deryabina; Darina Malygina; Nadezhda Plotnikova; Anna Solovyeva; Kseniya Belyaeva; Nina Melnikova (MDPI AG, 2018)
The activity of betulin-3,28-diphosphate (BDP) in combination with the cytostatics such as 5-fluorouracil (5-FU) and hydrazine sulfate (HS) was demonstrated by using the transplanted Ehrlich ascites carcinoma (EAC) in mice. The dose-dependent effect of combination drugs BDP + HS and BDP + 5-FU was revealed by in vitro experiments on rats. The synergetic effect of HS and BDP on oxidative stress and energy metabolism was established. The malonic dialdehyde (MDA) level both in plasma and erythrocytes decreased by 87 ± 2%, and the superoxide dismutase (SOD) activity increased by 105 ± 7% in comparison with the control. The combination of BDP + HS promoted the increase of lactate dehydrogenase (LDH) activity in the reverse reaction by 195 ± 21% compared to the control. The combination drug of 5-FU with BDP caused the synergetic decrease of the lipid peroxidation (LPO) intensity estimated by the MDA level decrease up to 14 ± 4% compared to pure compounds. Betulin-3,28-diphosphate in combination with cytostatics for EAC treatment improved the animal health status, as well as decreased the cytostatics dose that can be used in palliative therapy.